Assessing the Managerial Challenge of Balancing Social and Economic Responsibilities in the Food Retail Industry: A Company Based Qualitative Case Study - Guice, Lindsey (2017)
This study seeks to explore the challenge of balancing social and economic needs as a manager in the food retail industry. The focus on the food retail industry is due to the fact that the business is heavily reliant on production from the environment. Research within this study is intended to investigate why the industry managers need to address social issues, why it can be a challenge, and question if they can effectively balance their social responsibilities with their economic responsibilities. The structure introduces the topic through a review of literature then transitions into methodology with the application of a case study. The case study focuses on a company that is a proven leader within the industry and can set precedent for other food retailers alike. Theories that are present in the literature and methodology will come together later in the study and be compared during analysis. The purpose of the study is to first review what has already been written on the subject, then use primary qualitative research to expose a part of the conversation that has been left unsaid, and finally conclude the study’s finding with a fuller understanding and reasoning behind the managerial challenge.